2015
DOI: 10.1016/j.molliq.2015.06.008
|View full text |Cite
|
Sign up to set email alerts
|

Molecular dynamics simulations of liquid crystalline phases of dodecyltrimethylammonium chloride

Abstract: The formation of a second phase in presence of a crack in a crystalline material is modelled and studied for different prevailing conditions in order to predict and a posteriori prevent failure, e.g. by delayed hydride cracking. To this end, the phase field formulation of Ginzburg-Landau is selected to describe the phase transformation, and simulations using the finite volume method are performed for a wide range of material properties. A sixth order Landau potential for a single structural order parameter is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
13
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 61 publications
2
13
0
Order By: Relevance
“…This result is consistent with scattering and NMR studies and other reports on the elliptical profile for rod‐like micelles . On the other hand, a close contact among the rods in DTAC forces the individual rods into having a hexagonal profile, in agreement with the previous studies …”
Section: Resultssupporting
confidence: 93%
See 4 more Smart Citations
“…This result is consistent with scattering and NMR studies and other reports on the elliptical profile for rod‐like micelles . On the other hand, a close contact among the rods in DTAC forces the individual rods into having a hexagonal profile, in agreement with the previous studies …”
Section: Resultssupporting
confidence: 93%
“…in DTAC forces the individual rods into having ah exagonal profile, in agreement with the previous studies. [12] Our MD simulations confirmed that at high concentration of water DTAC rods becomeu nstable. For instance, an MD simulation on as ingle rod with 50 wt %r esulted in its rapid decompositioni ntoi rregular micelles at times < 5ns.…”
Section: Figure 8p Resentst He Snapshots Of Equilibrated Structures Osupporting
confidence: 66%
See 3 more Smart Citations